The Influence of Clusterin Glycosylation Variability on Selected Pathophysiological Processes in the Human Body. (28th August 2022) - Janiszewska, Ewa; Kmieciak, Agnieszka; Kacperczyk, Monika; Witkowska, Aleksandra; Kratz, Ewa Maria
Abstract : The present review gathers together the most important information about variability in clusterin molecular structure, its profile, and the degree of glycosylation occurring in human tissues and body fluids in the context of the utility of these characteristics as potential diagnostic biomarkers of selected pathophysiological conditions. The carbohydrate part of clusterin plays a crucial role in many biological processes such as endocytosis and apoptosis. Many pathologies associated with neurodegeneration, carcinogenesis, metabolic diseases, and civilizational diseases (e.g., cardiovascular incidents and male infertility) have been described as causes of homeostasis disturbance, in which the glycan part of clusterin plays a very important role. The results of the discussed studies suggest that glycoproteomic analysis of clusterin may help differentiate the severity of hippocampal atrophy, detect the causes of infertility with an immune background, and monitor the development of cancer. Understanding the mechanism of clusterin (CLU) action and its binding epitopes may enable to indicate new therapeutic goals. The carbohydrate part of clusterin is considered necessary to maintain its proper molecular conformation, structural stability, and proper systemic and/or local biological activity. Taking into account the wide spectrum of CLU action and its participation in many processes in the human body, further studies on clusterin glycosylation variability are needed to better understand the molecular mechanisms of many pathophysiological conditions. They can also provide the opportunity to find new biomarkers and enrich the panel of diagnostic parameters for diseases that still pose a challenge for modern medicine.